Man, Space and Nature. The Bay of Kotor in the Prose of Nikola Malović - Nowak-Bajcar, Sylwia (Poznańskie Studia Slawistyczne, 2022)
The article presents the imaginary structure of The Bay of Kotor in selected works ( the novels: Latajući Bokelj [Wandering Bokelj], Jedro nade [Sail of Hope] and the collection of short stories Prugastoplave storije [Striped Blue Stories]) by Nikola Malović, as well as the issues of ideological consequences of this literary creation, in which the region becomes a metonymy for the problems of the modern world. The story of the Bokelian identityis a story about rooting, about space treated as oikos, and about a man as one of the elements of this system. In Malović’s reflection, the awareness of the writer’s place of origin is combined with the awareness of responsibility for it. Looking for the disastrous consequences for humans in the interdependence between power ( politics ) and knowledge ( civilization development ), in returning to the tradition and experiences of ancestors, he sees an antidote to the devastating activity of man, which links this concept with the current of research referred to as traditional ecological knowledge.